DETECTION OF URER AND UREC AMONG PROTEUS MIRABILIS - ABDUL KAREEM MUNEER ALATRASH,; AHLAM KADHUM AL-YASSEEN, (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to investigate the correlation between ureR and ureC genes with the production of urease by Proteus mirabilis. Methods: A total of 450 mid-stream urine samples have been collected from patients with urinary tract infection whom admitted to the hospitals in Annajaf Al-Ashraf province for consultancy during the period from October 2015 to February 2016.Out of 150 bacterial isolates, only 29 isolates were belong to P. mirabilis according to conventional methods (depending on microscopic and culturing examination as well as biochemical test) and molecular technique using 16SrRNA gene. Results: The results of phenotypic and genotypic detection of urease in P. mirabilis showed that all isolates were able to produce urease and possess ureR and ureC that encodes to urease by appearing of amplicon with molecular weight 359 and 533 bp, respectively, when electrophoresed on 1% agarose gel. Conclusion: A correlation has been found between ureR and ureC genes with the production of urease by P. mirabilis.